Misconceptions in Physics among High School Teachers: A Case Study in Dire Dawa City, Ethiopia - Belay Sitotaw Goshu; Melaku Masresha Woldeamanueal; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2025)
Ensuring high-quality education depends heavily on teacher competency. Diagnostic exams can assess teachers' topic knowledge and identify areas where they need to improve their preparation. Nonetheless, gender and education level-based performance gaps underscore the need for a more thorough comprehension of these variables in the Ethiopian educational setting. The purpose was to assess teachers' performance on a diagnostic exam given by standards established by the Ethiopian Ministry of Education and investigate performance differences by gender and educational attainment. Existing studies on teacher competency in Ethiopia have rarely explored the influence of demographic variables, leaving a critical gap in understanding how gender and education level impact performance. Methodology: A cross-sectional analysis was conducted using diagnostic test scores of teachers. The relationships between education level, gender, and performance were assessed using statistical techniques such as correlation analysis, t-tests, and chi-square testing. Teachers with an MSc outperformed those with a BSc, with average scores of 75 and 62, respectively. Female teachers passing rate was (62.1%) and the male teachers (68.9%), but the chi-square test indicated no statistically significant association between gender and performance (χ² = 0.05, p = 0.824). Significant disparities in diagnostic test performance highlight gaps in teacher preparedness. Tailored training programs, equitable resource allocation, and gender-sensitive strategies are recommended to improve teacher performance and bridge identified gaps.